Laser Forming and Welding Processes - Yilbas, Bekir Sami.; Akhtar, Sohail; Shuja, Shahzada Zaman; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
This book introduces model studies and experimental results associated with laser forming and welding such as laser induced bending, welding of sheet metals, and related practical applications. The book provides insight into the physical processes involved with laser forming and welding. The analytical study covers the formulation of laser induced bending while the model study demonstrates the simulation of bending and welding processes using the finite element method. Analytical and numerical solutions for laser forming and welding problems are provided.
Introduction to Laser Forming and Welding Processes -- Analytical Treatment of Laser Forming and Welding Processes -- Numerical Analysis for Laser Forming and Welding -- Experimental Analysis for Laser Forming and Welding -- Concluding Remarks.
Keywords: Engineering; Structural control (Engineering).; Surfaces (Physics).; Engineering; Operating Procedures, Materials Treatment; Surfaces and Interfaces, Thin Films; Laser Technology, Photonics